2016
DOI: 10.1021/acs.est.5b03097
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Brittle Failure Envelopes of Individual Reaction Zones Observed in CO2-Exposed Wellbore Cement

Abstract: To predict the behavior of the cement sheath after CO2 injection and the potential for leakage pathways, it is key to understand how the mechanical properties of the cement evolves with CO2 exposure time. We performed scratch-hardness tests on hardened samples of class G cement before and after CO2 exposure. The cement was exposed to CO2-rich fluid for one to six months at 65 °C and 8 MPa Ptotal. Detailed SEM-EDX analyses showed reaction zones similar to those previously reported in the literature: (1) an oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…One is the wide and weak CH-depleted zone, characterized by increased porosity due to dissolution of CH. The CH-depleted zone has also been observed in previous studies and, in some cases, was noticeably wide. ,,, However, the factors that control the widening of this zone during the reaction are not clear, and thus, it is uncertain how the width of this zone can be limited for designing a better wellbore cement material.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…One is the wide and weak CH-depleted zone, characterized by increased porosity due to dissolution of CH. The CH-depleted zone has also been observed in previous studies and, in some cases, was noticeably wide. ,,, However, the factors that control the widening of this zone during the reaction are not clear, and thus, it is uncertain how the width of this zone can be limited for designing a better wellbore cement material.…”
Section: Introductionmentioning
confidence: 61%
“…In addition to characterizing chemical reactions that take place during GCS, several studies have focused on the (hydro)­mechanical property changes of cement after CO 2 exposure ,,,, In our recent study, we found that two important zones in CO 2 -attacked cement are related to the decrease of cement strength and, thus, deserve more attention. One is the wide and weak CH-depleted zone, characterized by increased porosity due to dissolution of CH.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As dissolution and precipitation proceed, the radii are calculated and updated each time step. For each segment, R PCC ( t ) is calculated by assuming that the portlandite-depleted cement is separated from the unreacted cement core by a sharp reaction front 46 , 51 ( Figure 2 c). This gives , where ξ P [-] is the extent of portlandite dissolution in the segment volume.…”
Section: Modeling Approachmentioning
confidence: 99%
“…The permeation of CO2-bearing fluids accompanied by so-called carbonation process (Scherer and Huet, 2009;Huet, Tasoti and Khalfallah, 2011;Kari, Puttonen and Skantz, 2014;Ashraf, 2016;Šavija and Luković, 2016;Rezagholilou, Papadakis and Nikraz, 2017). This process results in the formation of calcium carbonate (hereafter referred to as calcite) within the cement pores which reduces the porosity and increases the cement stiffness (Kutchko et al, 2009;Mason et al, 2013;Nakano et al, 2014;Walsh et al, 2014;Ashraf, 2016;Hangx et al, 2016). The invasion of more quantity of CO2-bearing fluids into the cement matrix re-dissolve calcite and calcium silicate hydrate (C-S-H) which leads to the stiffness reduction and an increase in the porosity (Kutchko et al, 2007;Huerta, Bryant and Conrad, 2008;Rimmelé et al, 2008;Fabbri et al, 2009;Duguid and Scherer, 2010;Lecampion et al, 2011;Brunet et al, 2013;Zhang et al, 2013;Walsh et al, 2014;Liaudat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%